Empirical study on the impact of lean production practices on firms performace in Malaysian manufacturing industries - Iteng, Rosman; Ahmad, Mohd Akhir; Abdul Rahim, Kamarul Irwan; Mad Lazim, Halim (2018)
The purpose of the paper is to examine the significance of incorporating lean production (LEAN) in the Malaysian manufacturing industry. Lean production investigated in this paper consists of eight practices namely supplier focus, employee focus, continual improvement, customer focus, quality at source, just-in time, flow system and technology & innovation.This study utilizes two hundred and five manufacturing companies, selected randomly from the Federation of Malaysian Manufacturers Directory.The study measures senior production or lean managers‟ perception of the lean production practices and the level of quality performances in their companies.Grounded by the Program Theory, this paper specifically investigates whether the implementation of lean production practices will affect the quality performance in the organization.Pearson‟s correlations exhibit significant correlations between the eight lean practices and quality performance measures (measured by product conformance, product performance and product reliability). The findings of the study provide a striking demonstration of the importance of lean practices in enhancing the quality performances of the Malaysian manufacturing companies.The result indicates that manufacturing companies will enjoy the benefit of improving quality performance from the utilization of lean practices.